Management of Hemorrhagic Pseudoaneurysmal Arteriovenous Fistula of the Sphenopalatine Artery - Ajeet Gordhan (Case Reports in Vascular Medicine)
n-Butyl cyanoacrylate (n-BCA) embolization of a hemorrhagic pseudoaneurysmal arteriovenous fistula of the sphenopalatine artery in a patient with paranasal sinus squamous cell carcinoma treated with regional surgery and radiation has, to our knowledge, not been previously reported.